Performance Improvement of PT. Bintang Citra Utama in Gorontalo District - Aprilia Mohu (Journal of Management and Administration Provision, 2021)
This study aims to obtain a picture of PT. Bintang Citra Utama in Gorontalo Regency. The research method uses a qualitative type with a qualitative approach. Data collection techniques carried out through interviews with several informants and observations and recording secondary data related to research problems. The results of the study concluded that employee performance was not optimal because there were still delays in completing work. Employees are not left independent to solve problems. So employees depend on the leadership. The quality of work is not optimal so it must be maximized according to the ability of employees. Work quantity still needs to be reviewed again because the workload is very influential in the speed and completion of work. So it also affects the delay in completing work. Responsibility in the work is not optimal because there are still hands-off with work, and employee discipline to obey the rules that have been set is still lacking.